Search for the Higgs boson in the H → WW(∗) → ℓ+νℓ−ν decay channel in pp collisions at √s = 7 TeV with the ATLAS detector - Anduaga, Xabier Sebastián (2012)
A search for the Higgs boson has been performed in the H → WW(∗) →ℓ+νℓ−ν channel (ℓ= e/μ) with an integrated luminosity of 2.05 fb−1 of pp collisions at √s = 7 TeV collected with the ATLAS detector at the Large Hadron Collider. No significant excess of events over the expected background is observed and limits on the Higgs boson production cross section are derived for a Higgs boson mass in the range 110 GeV < mH < 300 GeV. The observations exclude the presence of a Standard Model Higgs boson with a mass 145 < mH < 206 GeV at 95% confidence level.